Bactofection of sequences encoding a Bax protein peptide chemosensitizes prostate cancer tumor cells - Marco Antonio Hernández-Luna; Ricardo Díaz de León-Ortega; Daniel Dimitri Hernández-Cueto; Ricardo Gaxiola-Centeno; Raúl Castro-Luna; Leonel Martínez-Cristóbal; Sara Huerta-Yépez; Rosendo Luria-Pérez (Permanyer, 2016)
Background: Tumor cell resistance to chemotherapy agents is one of the main problems in the eradication of different neoplasias. One of the mechanisms of this process is the overexpression of anti-apoptotic proteins such as Bcl-2 and Bcl-XL; blocking the activity of these proteins may contribute to the sensitization of tumor cells and allow the adequate effects of chemotherapeutic drugs. Methods and results: This study adressed the transfection of prostate cancer cells (PC3) with a plasmid encoding a recombinant protein with an antagonist peptide from the BH3 region of the Bax protein fused to the GFP reporter protein (BaxGFP). This protein induced apoptosis of these tumor cells; further, selective transport of this plasmid to the tumor cell with Salmonella enterica serovar Typhimurium (strain SL3261), a live-attenuated bacterial vector, can induce sensitization of the tumor cell to the action of drugs such as cisplatin, through a process known as bactofection. Conclusions: These results suggest that Salmonella enterica can be used as a carrier vector of nucleotide sequences encoding heterologous molecules used in antitumor therapy.